The effect of initial pressure on the thermal behavior of the silica aerogel/PCM/CuO nanostructure inside a cylindrical duct using molecular dynamics simulation - Yuanfei Gao; Ali Basem; S. Mohammad Sajadi; Dheyaa J. Jasim; Navid Nasajpour-Esfahani; Soheil Salahshour; Shadi Esmaeili; Sh. Baghaei (Case Studies in Thermal Engineering, 2024)
Amidst escalating fuel expenses and growing concerns over greenhouse gas pollution, the adoption of renewable alternative energy sources has become increasingly imperative. In response, scientists are fervently dedicated to identifying energy-saving solutions that are readily adaptable. Notably, silica aerogels have demonstrated remarkable efficacy in temperature management under both hot and cold conditions, while phase change materials are renowned for their capacity to store thermal energy. The study examines the effect of initial pressure on the thermal performance of silica aerogel/PCM/CuO nanostructure in a cylindrical duct. This was investigated using MD simulations and the LAMMPS software. The study will investigate several elements, such as density, velocity, temperature patterns, heat flux, thermal conductivity, and charge time or discharge time of the simulated structure. According to the results, with an increase in the initial pressure, the maximum density increases from 0.0838 atom/Å3 to 0.0852 atom/Å3, and the maximum velocity decreases from 0.0091 Å/fs to 0.0081 Å/fs. Also, the findings show that, by increasing the initial pressure, the temperature decreases from 931.42 K to 895.63 K, and thermal conductivity and heat flux decrease to 1.56 W/m.K and 56.66 W/m2 with increasing the initial pressure to 5 bar. Finally, the results show that charging time increases to 6.34 ns at 5 bar. The increase in charging time with increasing initial pressure may be attributed to the reduced mobility of particles within the structure as a result of the higher pressure. The findings of this study can help for a better understanding of energy-saving solutions, advanced thermal management systems, and the design of efficient energy storage technologies tailored to specific pressure-related operating conditions.